Hacia un sistema latinoamericano de seguridad regional - Tomassini, Luciano (Estudios Internacionales, 1982)
Currently the link between the increase in our "external insecurity" and the presence of the so-called "national security" regimes in many Latin American countries is evident. We can clearly see that these regimes have ended up eroding the foundations of our stability and autonomy, in such a way that it is obvious to broad sectors that the reconquering of these values requires the reestablishment of democracy in Latin America. There is an urgent need to move towards the establishment of a Latin American regional security system based on the strengthening of democracy internally and in the search for a reasonable margin of autonomy at the level of international relations. In this paper some suggestions are made regarding the background, content and results that the analysis of this problem could have.